The Lysine Methyltransferase G9a in Immune Cell Differentiation and Function - Scheer, Sebastian; Zaph, Colby (Frontiers in Immunology, 2017)
G9a (KMT1C, EHMT2) is a lysine methyltransferase (KMT) whose primary function is to di-methylate lysine 9 of Histone H3 (H3K9me2). G9a-dependent H3K9me2 is associated with gene silencing and acts primarily through the recruitment of H3K9me2-binding proteins that prevent transcriptional activation. Gene repression via G9a-dependent H3K9me2 is critically required in embryonic stem (ES) cells for the development of cellular lineages by repressing expression of pluripotency factors. In the immune system, lymphoid cells such as T cells and innate lymphoid cells (ILCs) can differentiate from a naïve state into one of several effector lineages that require both activating and repressive mechanisms to maintain the correct gene expression program. Furthermore, long-term immunity to re-infection is mediated by memory T cells, which also require specific gene expression and repression to maintain a quiescent state. In this review, we examine the molecular machinery of G9a-dependent functions, address the role of G9a in lymphoid cell differentiation and function, and identify potential functions of T cells and innate lymphoid cells that may be controlled by G9a. Together, this review will highlight the dynamic nature of G9a-dependent H3K9me2 in the immune system and shed light on the nature of repressive epigenetic modifications in cellular lineage choice.